Indonesian Syntactic Interference on the English Speaking Skills of Non-English Major Students - Amir hamzah; amirhamzah@institutpendidikan.ac.id; Wahid Hasyim (Journal Civics And Social Studies, 2021)
This research aims to analyze Indonesian syntactic interference on the English Speaking Skills of Non-English Major Students. The research subjects were 3rd semester level 2 students at one of the non-English majoring universities in Garut. This research uses a qualitative descriptive approach with matching and distributional methods. Meanwhile, the corpus was obtained using listening techniques (SBLC), recording and taking notes from student conversation assignments about their past activities in video form. The results show that syntactic interference in this study includes inaccurate word forms influenced by the past tense, inaccurate subject-verb agreement, non-parallelism, absence of articles, sentence patterns that do not match S + P + O, inaccurate use of the words 'no' and 'not'.